Comparative analysis of broilers growing in different maintenance systems - Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In Romania it is necessary to pay special attention to adapt the broilers growing and exploitation systems to the European Union requirements. At the same time, it is necessary to protect and stimulate those characteristics of chickens growing and exploitation that have competitive advantages concerning the obtained products quality and the minimum environmental impact technologies. An especially important desideratum is to promote and implement the environmentally friendly production systems. It is important that technological solutions adopted in the growth and exploitation of poultry to meet all environmental requirements, for the conservation of natural area of Romania. The main objective of this work is to provide a technical economic solution for broilers growing both in intensive and in household or ecological system. Our researches reveal that the intensive - industrial system of broilers growing remains the main source to satisfy the global and the national consumption. The alternative technologies of chicken growing, in particular the ecological system, take place on the domestic poultry market, but it is necessary to create slow-growing biological material, fodder with components allowed by this technology, certified organic slaughterhouses and should develop a specific market segment. Farmer's yard chicken will still remain in the Romanian countryside. Householders must change their mentality and approach the peasant poultry farming from more economic positions.
Keywords: 330; chicken; growth; production; intensive; ecological